2013
DOI: 10.1111/aas.12064
|View full text |Cite
|
Sign up to set email alerts
|

Serious complications associated with spinal and epidural anaesthesia in Finland from 2000 to 2009

Abstract: In this closed claims analysis, major problems related to neuraxial blocks were rare. Epidural or a combined spinal and epidural technique resulted in more complications than did spinal procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 50 publications
(68 reference statements)
2
66
0
6
Order By: Relevance
“…The risk of neuraxial haematoma was far greater with epidural analgesia (1 : 26 400) than spinal anaesthesia (1 : 775 000). 56 A much higher risk was noted in a recent audit report of over 35 000 patients from the USA: cardiac arrest 1 : 5000, epidural abscess 1:27 000 and epidural haematoma 1 : 5400. 57 In making the decision to use epidural analgesia, the failure rate has to be taken into consideration.…”
Section: Regional Anaesthesia Techniquesmentioning
confidence: 92%
“…The risk of neuraxial haematoma was far greater with epidural analgesia (1 : 26 400) than spinal anaesthesia (1 : 775 000). 56 A much higher risk was noted in a recent audit report of over 35 000 patients from the USA: cardiac arrest 1 : 5000, epidural abscess 1:27 000 and epidural haematoma 1 : 5400. 57 In making the decision to use epidural analgesia, the failure rate has to be taken into consideration.…”
Section: Regional Anaesthesia Techniquesmentioning
confidence: 92%
“…21 There were 28% to 45% of patients in different groups needed a rescue antipruritic agent such as naloxane. Recently, Pitkanen and coworkers 22 revealed that the rate of fatality and neuraxial hematoma are significantly higher in epidural and CSEA than spinal anesthesia. The lateral holes of the epidural catheter may lie near to the dural puncture site; thus, injection of a bolus solution of drug through the epidural catheter has the potential risk of leakage from the dural puncture into the subarachnoid space.…”
mentioning
confidence: 99%
“…The incidence of epidural hematoma is 1:26,000 [39] and the risk of epidural abscess is 0.014% [40].…”
Section: Anesthesia For the Intestinal Transplant Living Donormentioning
confidence: 99%